THE PHENOMENOLOGICAL TRADITION IN RUSSIAN PHILOSOPHY - Schastlivtseva, Elena; Kazakova, Natalya (Revista Inclusiones, 2020)
The purpose of this article is the historical and philosophical reconstruction of phenomenological tradition in Russian philosophy of the late XIX - first half of the ХХ century; to reveal its epistemological specifics. We disclose the issue of phenomenological philosophy in Russia, its significant influence was rendered by immanentism and organicism. According to our hypothesis, it is the organic understanding of the world that becomes the main idea of the new philosophical worldview in XX century. The organic understanding of the world was inherent in the most prominent representatives of Russian philosophy such as N.E. Lossky and S.L. Frank, as well as the neoKantian S. Hesse. It is largely determined by their egotological perception.